Degradation of the herbicide tebuthiuron using solar photo-Fenton process and ferric citrate complex at circumneutral pH - Silva, M. R. A.; Trovo, A. G.; Nogueira, R. F. P. (Elsevier B.V., 2007)
The influence of pH on the degradation of the herbicide tebuthiuron (TBH) was investigated using in situ generated Fe(III)-citrate complexes (Fe:cit) submitted to the photo-Fenton process under solar irradiation. Using Fe:cit in a wide pH range (2.5-7.5), 100-78% TBH oxidation was achieved respectively from a UV dose of 2.0 J cm(-2) (15 min). Moreover, the oxidation of TBH obtained in the presence of Fe:cit at pH 6.0 was higher than that obtained using Fe(NO3)3 at pH 2.5. A similar behavior is observed for the removal of total organic carbon (TOC) in TBH solutions. In the presence of Fe:cit, 20% and 85% of TOC was removed at pH 7.5 and 2.5, respectively, after 7.5 J cm-2 irradiation, while no mineralization was observed employing Fe(NO3)(3) for the same UV dose. Using Fe(NO3)(3), mineralization was observed only after 11 J cm-2 (8%). A higher mineralization rate was obtained with Fe(NO3)(3) only when a concentration three times higher was employed at pH 2.5. Besides the high efficiency of TBH degradation observed using the ferric citrate complex in the solar photo-Fenton process, it also offers the advantage of application at a pH of up to 7.5. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: advanced oxidation processes; complexes; herbicides; photolysis